ANALYSIS OF THE DEVELOPMENT OF PHYSICS IN THE XXI CENTURY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the 21st century, physics continues to occupy a key place in scientific progress and technological development of mankind. This article examines the main directions and achievements of physics over the past two decades, including nanophysics, quantum technologies, astrophysics, as well as the impact of the discovery of new particles and phenomena on our understanding of the universe.